Optical properties of individual GaN nanorods for light emitting diodes: Influence of geometry, materials, and facets - Koelper, C.; Sabathil, M.; Witzigmann, Bernd; Roemer, F.; Bergbauer, W.; Strassburg, M. (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
We present a systematic analysis of the optical properties of GaN nanorods (NRs) for the application in Light Emitting Diodes (LEDs). Our focus is on NR emitters incorporating active layers in the form of quantum-disc or core-shell geometries. We concentrate on the properties of individual NRs, neglecting any coupling with neighbouring NRs or ensemble effects. The distribution of power among guided and radiative modes as well as Purcell enhancement is discussed in detail in the context of different NR geometries, materials and the presence of interfaces. © 2011 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Beam shaping; Extraction efficiency; GaN; LED; Nanorods; Nitrides; Optical waveguide; Purcell effect